THE DISTRIBUTION OF HOME MORTGAGES BY COMMERCIAL BANKS, ISLAMIC BANKS, AND RURAL BANKS DURING THE COVID-19 PANDEMIC - Annisa Rahima (Jurnal REP (Riset Ekonomi Pembangunan), 2023)
This research aimed to examine the distribution of home mortgages by various banks, i.e., commercial banks, Islamic banks, and rural banks during the 2-year Covid-19 pandemic in Indonesia. This study used panel data as the analysis method and the variables consisted of Residential Property Price Index (RPPI) and interest rates. The regression results showed that RPPI had a positive but not significant effect on the distribution of home mortgages during the pandemic. From the regression results, it is found that IHPR has an insignificant effect on KPR distribution during the pandemic. That is, when property prices increase, it will not affect the distribution of mortgages provided by commercial banks, Islamic banks and rural banks. Loan interest rates also have no significant effect on mortgage distribution during the pandemic. This implies that when the loan interest rate increases, it does not affect the distribution of mortgages provided. However, the increase in mortgage distribution during the Covid-19 pandemic is due to government efforts through subsidized mortgage policies such as Loan to Value (easing credit limits), VAT exemption incentives and expanding these policies not only in banks but also to rural banks.